Analisis Implementasi dan Keberlanjutan Bisnis Riche Shoes di Kota Palembang - Cessya Auwdrya; Yulizar Kasih (Universitas Multi Data Palembang, 2026)
This study aims to analyze the implementation and business sustainability of Riche Shoes Perfume and Cleaner as a shoe care business. Riche Shoes Perfume and Cleaner introduces product innovation in the form of a 2-in-1 shoe cleaner and deodorizer in a single package to enhance practicality and increase consumer appeal. The research employs a descriptive method with qualitative and quantitative approaches, with data collected through direct observation of business operational processes and the distribution of questionnaires to measure customer satisfaction levels. The results show that the implementation of Riche Shoes Perfume and Cleaner has been fairly effective in terms of the production process, financial report analysis, marketing strategies, and customer service. From a business sustainability perspective, this business demonstrates strong potential supported by product innovation, affordable pricing, appropriate marketing strategies, and effective financial management, enabling Riche Shoes Perfume and Cleaner to continue growing and competing as an MSME in the shoe care industry.